El cultivo de plátano (Mussa balbisiana) y la calidad ambiental del suelo, caso hacienda San Rafael - Loor Villamil, Roney Andrés (2016)
The research was conducted at the Hacienda San Rafael Canton El Carmen, Manabí province and aimed to determine the incidence of productive activities of plantain cultivation on soil quality, once the processes performed in identified the study area, proceeded to raise the indicators to begin should be simple, reliable, economical and very sensitive to soil management, these indicators were physical (texture) and chemical (organic matter, pH, content NPK), it was possible compare these results to the general guide to the interpretation of soil analysis were used to determine the quality indices, giving reliable, accurate results within an acceptable range, and to facilitate their understanding and use. The indicators made for the study indicates that testing should be able to measure soil quality properties, which are meaningful to the user, according to the understanding of soil and its processes. In the end it was found that the uncultivated land area has a quality index of 0.65 placing it in a category of high quality and land area cultivated with balbisiana mussa presents a quality index of 0.35 placing it in a Low quality category, concluding that plantain production activities adversely affect soil quality.